Inhalation of the novel tryptophan hydroxylase 1 inhibitor TPT-004 alleviates pulmonary arterial hypertension - Legchenko, Ekaterina; Chouvarine, Philippe; Hysko, Klea; Qadri, Fatimunnisa; Wesolowski, Radoslaw; Specker, Edgar; Glage, Silke; Meier, Martin; Schwarz, Katharina; Heineke, Jörg; Pohlmann, Gerhard; Ramazanoglu, Mehmet; et al. (American journal of respiratory cell and molecular biology, 2025)
Inhaled pharmacotherapies are promising treatment options for patients with pulmonary arterial hypertension (PAH), as they minimize extrapulmonary adverse effects. Recently, we developed a highly specific tryptophan hydroxylase 1 inhibitor (TPHi): TPT-004. We hypothesized that repetitive nose-only inhalation of TPT-004 alleviates PAH and pulmonary vascular remodeling in the Sugen 5416/hypoxia (SuHx) rat model. Male Sprague Dawley rats were divided into three groups: ConNx (control animals kept in room air during the study); SuHx+vehicle (rats injected with the VEGFR2 inhibitor SU5416 and then exposed to chronic hypoxia for 3 weeks, followed by 10 days recovery and subsequent 4 weeks of daily vehicle inhalations; and SuHx+TPHi (SuHx-exposed rats after recovery treated with daily inhalations of the TPH1 inhibitor, TPT-004, for 4 weeks). Closed-chest right-left heart catheterization and cardiac magnetic resonance imaging were performed in spontaneously breathing rats. Histological and mRNA-sequencing analyses were performed on lungs. SuHx-exposed rats had severe PAH, right ventricle (RV) hypertrophy, and RV dilation. In comparison with SuHx-exposed rats, TPHi-treated SuHx rats had significantly lower RV systolic pressure (67.25 vs. 51.47 mm Hg; P < 0.0001), normalized RV end-systolic volume (182.6 vs. 105.1 μl; P < 0.0001), and improved RV ejection fraction by cardiac magnetic resonance imaging (47.9 vs. 66.8%; P < 0.0001). Inhaled TPT-004 did not affect left ventricular (LV) end-diastolic or systemic blood pressure. TPT-004 therapy reversed pulmonary vascular remodeling and alveolar macrophage infiltration. RNA sequencing unraveled TPHi-induced changes in pulmonary gene expression: increased cell adhesion as well as reduced cell motility and migration; suppressed extracellular matrix remodeling; modulated immune response; and suppressed pulmonary vascular remodeling by means of modulating proliferation, apoptosis, and homeostasis. Taken together, TPT-004 is an effective therapeutic PAH agent that does not cause any hemodynamic adverse effects in rodents, and thus, should be tested further towards a clinical phase 1b/phase 2 study in patients with PAH.
Ursprünglich veröffentlicht: 3. February 2025
Gesehen am 03.11.2025